ESTABLISHMENT OF FARMS IN THE REPUBLIC OF UZBEKISTAN - Sanjarbek Khamrajonovich Mamajonov (Journals Park Publishing, 2024)
The article provides a scientific analysis of the establishment of farm activity in the Republic of Uzbekistan during the years of independence, the reforms implemented by the government in the first and second stages of its development and their results on the basis of literature and archival sources.
Keywords: Collective farm, state farm, farm, rent, land, budget, hectare, entrepreneurship, national economy, professional college.